STUDI KINETIKA DAN KAPASITAS BIOSORPSI KROM (III) OLEH BIOMASA JAMUR KINETIKA DAN KAPASITAS BIOSORPSI KROM (III) OLEH BIOMASA JAMUR - Widayati, Tri
Abstracts: The biosorption of chromium (III) ions from aqueous solution by using the fresh fungal biomass Mucor meihi was investigated to study the kinetic and capacity profiles of chromium biosorption at various conditions. The biomass obtained from laboratory culture. The biosorption removal was also carried out by using a soil fungi Humicola grisea. The study indicated that the fresh fungal biomass of Mucor meihi exhibited reasonably high uptake capacities for chromium (III). The rate constants of the sorption at different conditions determined using the Lagergren equation, were found in the range 0,673-0,761 jam-'. The process isoterm verified by Langmuir and Freundlich model were indicate that the Freundlich isoterm yield a better correlation than the Langmuir. The maximum capacity constants (q.) estimated by the Langmuir model were in the range 12,034-45,66 mg/g with a coefficient correlation (R2) 0,8693-0,9708. The Freundlich capacity constants (lc) were in the range 0,516-2,179 mglg with a coefficient correlation (R2) 0,9383-0,9927. The results showed that biosorption kinetics and capacities were strongly dependant on the pH solution, ion and biomass concentration , and biomass diameter.The adsorbed metal ions were eluted from the biomass using different acid solutions. The desorption process efficiencies achieved up to 80% by using HNO3 IN.